A Comparative Analysis of Privacy Preserving Techniques in Online Social Networks - Kausar, Firdous; Al Beladi, Shoroq Odah (Discoveries in Agriculture and Food Sciences, 2015)
The world became a global village due to the great revolution in communication and network fields. The internet eases the communication process all over the world. The social network services, for example; Facebook, that occurred recently are considered one of the most essential and common outcomes due to this revolution. People from different ages, views, cultures, languages, religions, education levels, etc. from all over the world can easily communicate through the social networks. Furthermore; people can share their news and personal information with each other. It can be also noticed that the social network are extensively used, so the privacy issues within it is essentially to be considered. This privacy will prevent any illegal accessing for the user personal information which in turns will increase the users’ conviction to use these networks during their daily life and encourage the other people who have never use the services that are available for using by social networks. This paper analyses several techniques which provides the privacy for Online Social Networks including Reclaim, Safebook, K-Automorphism, Vis-à-vis and SPKA. These techniques are investigated and clarified in terms of their methods in addition to the advantages and drawbacks.